Do the illegal and legal rents of politicians affect municipal election outcomes? Empirical evidence. Issue 4 (4th July 2019) - Benito, Bernardino; Guillamón, María-Dolores; Ríos, Ana-María; Bastida, Francisco
ABSTRACT: This paper aims to analyse whether illegal (corruption) and legal rent extraction (high politicians' wages) affect electoral outcomes at municipal level. We use an initial sample of 145 Spanish municipalities over 50, 000 for two electoral periods: 2004–2007 (before the crisis) and 2008–2011 (during the crisis). Our findings show that neither illegal nor legal rent extraction impact on re-election in non-crisis times. However, we observe that citizens penalize legal rent extraction in the ballots during the crisis. Regarding the economic performance of the local governments, we find that its effect on re-election is important in non-crisis period. Nevertheless, in time of crisis, given that the economic situation is bad in general in the country, voters pay less attention to economic factors and focus on politicians' behaviour.